Boreal Agriculture Cannot Be Sustainable Without Food Sovereignty - Keske, Catherine (Frontiers in Sustainable Food Systems, 2021)
Food sovereignty encompasses the right of humans to have access to, and to produce, healthy and culturally appropriate food. Food sovereignty exists within the “social” pillar of sustainability and sustainable food production. Over time, and as a result of colonialism and neo-liberal food regimes, Indigenous food system patterns in boreal regions have been disrupted. Imports make local food production economically infeasible. The intersection of food sovereignty and international trade is understudied. Food insecurity cycles are likely to perpetuate without deliberate action and government intervention. Policies that facilitate local access, and ownership, of agriculture and food processing facilities may foster food sovereignty. Indigenous community governance, and agricultural practices, are critical to restoring environmental and social sustainability.